Implementing a Scoring Function Based on Interaction Fingerprint for Autogrow4: Protein Kinase CK1δ as a Case Study - Pavan, Matteo; Menin, Silvia; Bassani, Davide; Sturlese, Mattia; Moro, Stefano (Frontiers in Molecular Biosciences, 2022)
In the last twenty years, Fragment-Based Drug Discovery (FBDD) has become a popular and consolidated approach within the drug-discovery pipeline, due to its ability to bring several drug candidates to clinical trials, some of them even being approved and introduced to the market. A class of targets that have proven to be particularly suitable for this method is represented by kinases, as demonstrated by the approval of BRAF inhibitor Vemurafenib. Within this wide and diverse set of proteins, protein kinase CK1delta is a particularly interesting target for the treatment of several widespread neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis. Computational methodologies such as molecular docking are already routinely and successfully applied in fragment-based drug discovery campaigns alongside experimental techniques, both in the hit-discovery and in the hit-optimization stage. Concerning this, the open-source software Autogrow, developed by the Durrant lab, is a semi-automated computational protocol that exploits a combination between a genetic algorithm and a molecular docking software for de-novo drug design and lead optimization. In the present work, we present and discuss a modified version of the Autogrow code that implements a custom scoring function based on the similarity between the interaction fingerprint of investigated compounds to a crystal reference. To validate its performance, we performed both a denovo and a lead-optimization run (as described in the original publication), evaluating the ability of our fingerprint-based protocol to generate compounds similar to known CK1delta inhibitors based on both the predicted binding mode and electrostatic and shape similarity in comparison with the standard Autogrow protocol.